An Evaluation of Possible Scenarios for The Contemporary Turkish Economic Turbulence - Mumin, Mumin Ahmad Khan (Scimadly Publishing, 2024)
The current economic crisis is one of the most pressing issues confronting the Turkish economy and society. A country's economy is defined as the growth and productivity of a country's resources and the flow of those resources in a distributed structure, as the economy is the backbone of any country. A country's economy can develop through its infrastructure and industrial development. Due to some internal dynamics in 1994, Turkey was impacted by global economic crises and had started to experience its first financial crisis. As the ongoing problem is caused predominantly by one factor, the economic crisis, it will be stimulating to see how this factor can directly influence the financial situation. Hence, the article shows a comparative analysis through parallel evaluation how the sudden economic crisis increases on the global and domestic level in the Turkish economy. In addition to this context, this study also focuses on the economic fluctuation in modern Turkey and the depreciation of the Turkish Lira against the dollar. As the various kinds of literature show that, there have been several financial crises in the world, the effect of which has been manifested in developed countries and the world’s developing countries as well. During the recent economic crisis, the Turkish finance sector faced several serious challenges which impacted its performance, such as the Lira-to-Dollar exchange rate.